2010
DOI: 10.1111/j.1755-148x.2010.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 prevents progression of nevi to melanoma predominantly through cell cycle regulation

Abstract: p53 is the central member of a critical tumor suppressor pathway in virtually all tumor types, where it is silenced mainly by missense mutations. In melanoma, p53 predominantly remains wild type, thus its role has been neglected. To study the effect of p53 on melanocyte function and melanomagenesis, we crossed the ‘high-p53’ Mdm4+/− mouse to the well-established TP-ras0/+ murine melanoma progression model. After treatment with the carcinogen dimethylbenzanthracene (DMBA), TP-ras0/+ mice on the Mdm4+/− backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 72 publications
10
58
0
Order By: Relevance
“…5C), the major enzymes involved in BER (33,34). Our results are in agreement with other reports that accumulation of p53 in melanocytes or melanoma cells induces genes that regulate cell-cycle arrest rather than apoptosis and increases the expression of OGG1 in human fibroblasts (35,36).…”
Section: Discussionsupporting
confidence: 93%
“…5C), the major enzymes involved in BER (33,34). Our results are in agreement with other reports that accumulation of p53 in melanocytes or melanoma cells induces genes that regulate cell-cycle arrest rather than apoptosis and increases the expression of OGG1 in human fibroblasts (35,36).…”
Section: Discussionsupporting
confidence: 93%
“…The importance of p53 in suppressing melanoma growth is supported by the rapid proliferation of BRAFV600E containing melanocytes on loss of p53 function [36]. Also, p53 prevents progression of naevi to melanoma in a transgenic mouse model [37]. In agreement with this Avery-Kiejda et al observed abnormal expression of p53 downstream target genes, in particular pro-apoptotic genes including Bax and PIG3 in melanoma [38].…”
Section: Ink4asupporting
confidence: 72%
“…As previously mentioned, this protein is involved in maintaining genomic stability, and can enforce a G1 cell cycle arrest or induce apoptosis in response to cellular stresses (Harris and Levine, 2005). As outlined above, cell cycle arrest at the G1 phase is very important as it allows for cellular repair pathways to remove damage before DNA synthesis and cell mitosis can begin (Terzian et al, 2010). Conversely, p53-induced apoptosis helps eliminate potential tumour cell progenitors.…”
Section: The P53 Signalling Pathway In Keratinocytesmentioning
confidence: 99%